STATUS HUKUM DAN TANGGUNG JAWAB ANAK PERUSAHAAN PT (PERSEROAN TERBATAS) DALAM SUATU KELOMPOK PERUSAHAAN - RIA SINTHA DEVI (LP2MTBM MAKARIOZ, 2020)
Group companies or better known as conglomerates is a topic that always attracts attention, because the uncontrolled growth and development of group companies can lead to a monopoly on a business network. What is meant by a holding company or also called a holding company in Indonesian, is a company that aims to own shares in one or more other companies and / or regulate one or more other companies. Usually, a holding company has many companies engaged in very different business fields. The formulation of the problem in this study is What is the form of responsibility of the parent company for the problems caused by the subsidiary? What is the role and legal position of the parent company in the group of companies? What is the responsibility of the subsidiary company for the parent company if it loses? The research objective is to determine the form of responsibility of the parent company for problems caused by the subsidiary, to know the role and legal position of the parent company in the group of companies, to determine the responsibility of the subsidiary company to the parent company if it incurs losses.The results of this study are the parent company that can be liable for criminal liability for actions or problems committed by its subsidiary companies in the form of liability is the holding company that directly controls the subsidiary company and also actively operates in carrying out business activities. Moral responsibility is the burden of the good name held by the parent company in the business environment. In the event that the subsidiary is negligent or unable to fulfill its achievements, the parent company as the guarantor must repay the debt to the creditor (after demanding that the debtor's property be confiscated and sold to repay the debt). In a group company, every company enters into an agreement / agreement with a third party (creditor), then the company must pay it off without holding any liability to its parent company. If a loss occurs, the company is liability based on an error because the new parent company can be held responsible if it commits an error in the form of a parent company dominance over the subsidiary, an illegal act or breach of contract and an element of loss to another party. The parent company is held responsible if it is proven that the loss suffered by the subsidiary due to the intervention of the parent company in management and finance so that the subsidiary suffers a loss. Therefore, if there is an inadvertent action by the Board of Directors in managing the company, it can cause losses to the company. The loss can be seen from the failure to maintain the prudential nature of running the company. The director in charge is responsible for the company's losses. The research suggestion is, criminal liability against the parent company can be done if the subsidiary company does an action that is not a corporate action, where the act is a direct instruction or the result of a decision / policy made by the parent company as the controller of the company and the majority shareholder through the mechanism of the Meeting. General Shareholders (GMS).